DEVELOPMENT OF RSSI WIFI-BASED INDOOR POSITION TRACKING SYSTEM USING SMARTPHONE - Syahadati Ichwanda, Arsharizka
In recent years, the development of technology and smartphone users has increased dramatically every year. Smartphones produce a variety of services including indoor position tracking. Tracking is the observing of persons or objects on the move from user and supplying a timely ordered sequence of respective location data which capable to depicting the motion on a server display. Currently the most widely used method for localization is the Global Positioning System (GPS). However, GPS has limited compilation in the room due to signal degradation by building structures. Therefore, indoor position tracking is needed to provide a more appropriate position. Signals from a WiFi router can be used to track indoor position. This experiment uses the Received Signal Strength Indicator (RSSI) value of the WiFi router. Received Signal Strength Indicator (RSSI) is a measurement of the power present in the received radio signal. Fingerprint technique is used in Wi-Fi signal-based position tracking. The fingerprint technique does not need to know the location of the available Access Point (AP). The fingerprint technique uses the RSSI value to construct the fingerprint map. To estimate user position using a matching algorithm such as the K-Nearest Neighbor (K-NN) method. This method calculates the RSSI value between the fingerprint database and the real-time RSSI value from the smartphone. The results of estimated user position are placed on a web page, so this system can track the user position in real-time. This tracking system has an accuracy of up to 78% with an average error distance of less than 3 meters. Advantage of this system is it only utilizes the Wi-Fi router signal in a room and uses a smartphone. The server only uses a web page to track the user’s position anywhere at any time. Indoor position tracking can be used in various fields such as tracking patient movements, tracking employee mobilization activities in the office, asset tracking in warehouses, tracking someone activities in the airport, and others.